The History of the Book, Literary History, and Identity Politics in Canada - DeCook, Travis (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2002)
National literary histories, like the Literary History of Canada, generally tend to perform exclusions on the basis of class, gender, race, language, and ethnicity; the only way to correct such past hegemonic exclusions is to assert the cultural legitimacy of specific communities' writings by writing new literary histories. Book history can be important for uncovering texts' transmission and reception histories surrounding the engagement of colonized groups with Western textualities, for its concentration on the institutions that mediate our engagement with literature, and for taking into account the institutions and economic forces involved with canonicity. The newly-established History of the Book in Canada/Histoire du livre et de l'imprimé au Canada project (HbiC/HLIC) has a significant role to play in rethinking Canada's cultural pasts by incorporating work based on identity politics, thereby becoming a truly interdisciplinary and inclusive project.